Course experience as the predictor of career personal efficacy - Cerveza, Ryan L.; Laguardia, Jan Kenneth R.; Lapinid, Minie Rose C. (Institute of Advanced Engineering and Science, 2024)
Despite the proliferation of the culture of accreditation in the country, accreditation evaluations fail to capture authentic student course experience. This study aimed to assess the students’ course experience as to how it can contribute to increasing their career personal efficacy when employed in the work field. The 70 respondents were the education graduates of the college of education of a certain university in the past 6 years. The hierarchical multiple regression (HMR) was used to determine which of these domains can explain a statistically significant amount of variance to the career personal efficacy of the respondents. Correlation analysis r and the analysis of variance (ANOVA) were also employed to determine the relationships of the domains of course experience to career personal efficacy. Results revealed a high correlation between the six domains of course experience and career personal efficacy with good teaching, and clear goals and standards as the best factors among the domains of course experience which can predict career personal efficacy. It is recommended that administrators and policymakers should look into these two domains of the course experience to plan for the development goals of colleges and universities.